The psychological cycle of misinformation: an integrative model of legitimation perception in social networks - Nascimento, Ivan Kaminski Do (Frontiers in Social Psychology, 2025)
This theoretical article proposes an integrative model to understand the dissemination of misinformation on social networks, articulating three central pillars of social and cognitive psychology: overconfidence bias, social conformity, and cognitive dissonance. It is argued that these factors interact to favor the perception of legitimacy and repeated sharing of false information, even in the face of corrective evidence. The model describes a psychosocial cycle composed of exposure, judgment, action, dissonance, and rationalization. We identify theoretical conditions for the delegitimization of misinformation and analyze how the digital environment intensifies the described psychosocial mechanisms. The model contributes to theoretical reflection by articulating previously isolated constructs into an integrated explanatory theory, offering implications for both future research and practical interventions in combating misinformation.